Impact Of Covid -19 On Education In Manipur (Journal of Namibian Studies : History Politics Culture, 2023)
The COVID-19 pandemic affects the education system all over the world. Schools, colleges, universities and centres of higher learning are shut down as a controlling measure against the spread of the coronavirus. The closure brings problems for students, teachers, and parents. The COVID crisis has impacted all the citizens of the world with no discrimination. However, the depth of the impact has been felt differently across different sections of society; Marginalised sections have been impacted worst. This study takes up education sector in order to explore and understand the impacts on learning process of students during the closure of schools in pandemic period. The vulnerability of poor students from the COVID crisis is well highlighted in many reports. The closures due to COVID-19 have brought significant disruptions to education across India. The evidence from some of the findings indicates that the pandemic is giving rise to learning losses and increases in inequality. To reduce and reverse the long-term negative effects, the government needs to take up number of learning recovery program. This paper aims to assess the impact of the COVID-19 pandemic on the education more particularly in Manipur.